1984
DOI: 10.1070/qe1984v014n02abeh004691
|View full text |Cite
|
Sign up to set email alerts
|

Soliton generation in stimulated Raman scattering and excitation of polar optical phonons

Abstract: Autler-Townes splitting of photoelectron energy distributions in resonant twophoton ionisation is predicted using standard Heitler-Ma techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…In this paper we use the assumption that solitons can exist if, at least, three conditions are satisfied: 1) the asymptotical solution in form of solitons is found; 2) the results of transition regime are consistent with the ones found in the previous part; 3) the obtained results are stable with respect to small (weak) perturbations. In our previous paper we established the possibility of existence of the solitons in nonstationary SRS with excitation of polar optical phonons [12]. In the present work it has been shown that the results of the computer simulation of the system of nonlinear equations (see [12]) are consistent with the asymptotic solutions.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this paper we use the assumption that solitons can exist if, at least, three conditions are satisfied: 1) the asymptotical solution in form of solitons is found; 2) the results of transition regime are consistent with the ones found in the previous part; 3) the obtained results are stable with respect to small (weak) perturbations. In our previous paper we established the possibility of existence of the solitons in nonstationary SRS with excitation of polar optical phonons [12]. In the present work it has been shown that the results of the computer simulation of the system of nonlinear equations (see [12]) are consistent with the asymptotic solutions.…”
Section: Introductionsupporting
confidence: 65%
“…In our previous paper we established the possibility of existence of the solitons in nonstationary SRS with excitation of polar optical phonons [12]. In the present work it has been shown that the results of the computer simulation of the system of nonlinear equations (see [12]) are consistent with the asymptotic solutions. The computer simulation was provided in Sections 3 and 4.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The generation of three-wave solitons in the resonant LO-phonon-mediated interaction of two intense coherent polaritons is proposed in [47]. We considered the theory and computer simulation of simultons formation in stimulated Roman scattering by polaritons in dipole-active crystals [48] [49]. In past years progress was also achieved in the process of the realization of solitons at different frequencies [50] [51] [52].…”
Section: Introductionmentioning
confidence: 99%
“…In quasi-stationary case, in absence of phase modulation of any kind, and given pump field, the system of equations for the 2 ε (Stokes) and 3 ε (polariton) can be reduced to the following (see (11) and (13) coefficients. This system is the part of more complex system considered in [21].…”
mentioning
confidence: 99%